ANALYSIS OF STUDENTS' INTEREST TO CONTINUE HIGHER EDUCATION - Khadijah, Siti (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
This study aims to analyze the factors that affect the interests of students pursue higher education. Respondence of this study are 185 students from SMA Negeri 2 Tambang Kampar. Analysis of data using mean scores and multiple linear regression. The results showed that motivation, aspirations, wishes, school and family environment jointly significant effect on the interests of students pursue higher education. Variables that have the most significant influence is the motivation of students for higher education, due to high motivation will emphasize a strong interest in the students to pursue higher education. While the variables that had a significant influence is the school environment, the cause of alumni and peers do not support students to pursue higher education. Meanwhile, the school should provide constructive motivation to the students to pursue higher education and schools to provide complete information about college students.